Methods of locating optimum pitch - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
Most of the therapies of voice disorders are based on the belief that each person has an optimum pitch, at which the voice will be of good quality and will have a maximum intensity with the least expense of energy. And they concern themselves mainly with altering the habitual pitch level or making the case to use his optimum pitch (West, et al, 1957; Thurman, 1958; Van Riper and Irwin, 1958; Murphy, 1964; Greene, 1964).